Understanding controls on rapid ice-stream retreat during the last deglaciation of Marguerite Bay, Antarctica, using a numerical model - Jamieson, S.S.R.; Vieli, A.; Ó Cofaigh, C.; Stokes, C.R.; Livingstone, S.J.; Hillenbrand, C.-D. (Journal of Geophysical Research: Earth Surface, 2014)
Using a one-dimensional numerical model of ice-stream flow with robust grounding-line dynamics, we explore controls on paleo-ice-stream retreat in Marguerite Bay, Antarctica, during the last deglaciation. Landforms on the continental shelf constrain the numerical model and suggest retreat was rapid but punctuated by a series of slowdowns. We investigate the sensitivity of ice-stream retreat to changes in subglacial and lateral topography, and to forcing processes including sea-level rise, enhanced melting beneath an ice shelf, atmospheric warming, and ice-shelf debuttressing. Our experiments consistently reproduce punctuated retreat on a bed that deepens inland, with retreat-rate slowdowns controlled by narrowings in the topography. Sensitivity experiments indicate that the magnitudes of change required for individual forcing mechanisms to initiate retreat are unrealistically high but that thresholds are reduced when processes act in combination. The ice stream is, however, most sensitive to ocean warming and associated ice-shelf melting and retreat was most likely in response to external forcing that endured throughout the period of retreat rather than to a single triggering ‘event’. Timescales of retreat are further controlled by the delivery of ice from upstream of the grounding line. Due to the influence of topography, modeled retreat patterns are insensitive to the temporal pattern of forcing evolution. We therefore suggest that despite regionally similar forcing mechanisms, landscape controls significant contrasts in retreat behavior between adjacent but topographically distinct catchments. Patterns of ice-stream retreat in the past, present and future should therefore be expected to vary significantly.